Founders of the RAS: Charles Babbage. Issue 4 (1st August 2017) - Edmunds, Michael
Abstract : He designed the first computer, but he failed to build it and upset the prime minister, as Mike Edmunds recounts. Abstract : He may have designed the first computer, but he failed to build it and upset the prime minister, as Mike Edmunds recounts in his Brief Lives, celebrating the founders and history of the RAS.